A review of the prescribing culture of anti-depressants across government districts in Northern Ireland - Ruddock, Mark W.; Watt, Joanne; Kurth, Mary Jo; Lamont, John V.; Mooney, Laura; Fitzgerald, Peter (Frontiers in Drug Safety and Regulation, 2023)
patient was compared against constituency; patients in Belfast West and Belfast North, followed by Foyle, had the highest costs per patient, and the lowest IMD (most deprived).This review concludes that there has been no change in the prescribing culture for antianxiety or anti-depressants across Northern Ireland (2020 -2022). The cost of mood and anxiety medication per patient did not correlate with the index of multiple deprivation (IMD).Areas of low IMD trended to have higher spend. Is it now time to review the prescribing culture in Northern Ireland and offer greater support to our GPs to initiate a program of deprescribing and manage the well-being of our citizens?